Nasal Outcomes of Presurgical Nasal Molding in Complete Unilateral Cleft Lip and Palate - Emily M. Williams; Carla A. Evans; David J. Reisberg; Ellen A. BeGole (Hindawi Limited, 2012)
Objective. Short-term nasal forms following primary lip repair were compared between presurgical nasal molding and control groups. Aim. To compare nasal symmetry between patients that had nasal molding and lip repair with those that had only lip repair. Design. Retrospective case-control study Patients. Complete unilateral CL+P patients had basilar and frontal photographs at two time points: (1) initial (2) postsurgical. 28 nasal molding patients and 14 control patients were included. Intervention. Presurgical nasal molding was performed prior to primary lip repair in intervention group. No nasal molding was performed in control group. Hypothesis. Nasal molding combined with lip surgery repair according to the Millard procedure provides superior nasal symmetry than surgery alone for nostril height-width ratios and alar groove ratios. Statistics. Shapiro-Wilk test of normality and Student's 𝑡-tests. Results. A statistically significant difference was found for postsurgical nostril height-width ratio (𝑃<.05). No other statistically significant differences were found. Conclusions. Nasal molding and surgery resulted in more symmetrical nostril height-width ratios than surgery alone. Alar groove ratios were not statistically significantly different between groups perhaps because application of nasal molding was not early enough; postsurgical nasal splints were not utilized; overcorrection was not performed for nasal molding.